2005
DOI: 10.1080/02757540500117318
|View full text |Cite
|
Sign up to set email alerts
|

The physico-chemical and bacteriological quality of rainwater collected over different roofing materials in Ile-Ife, southwestern Nigeria

Abstract: Samples of bulk free-fall and roof-intercepted rainwater over five different roof types (iron-zinc corrugated sheets, concrete slate tiles, Adex/asbestos cement sheets, aluminium sheets, and thatch) were collected and analysed using standard methods with adequate quality-control and quality-assurance measures. The mean values of some of the investigated parameters for the roof-intercepted samples occurred within four continuous sets of ranges, viz: <0.11 mg l −1 (NH + 4 ), 0.11-1.00 mg l −1 (Na. The other para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 9 publications
1
29
0
3
Order By: Relevance
“…Other metals that have been studied but reported to be of low or less severe concentrations include cadmium, chromium, nickel and selenium (Förster, 1999;Melidis et al, 2007;Mendez et al, 2011). Other studies observed that the concentrations of Mg, Na, K, nitrate, nitrites, chloride, sulphate and ammonium were not significantly different among free fall rainwater , asbestos and Fe-Zn and aluminium metal sheets (Adeniyi and Olabanji, 2005;Mendez et al, 2011). In other studies, high concentration of nitrates and sulphates in roof runoff were largely attributed to fossil fuel combustion rather than roof materials (Mouli et al, 2005;Evans et al, 2006;Melidis et al, 2007;Gikas and Tsihrintzis, 2012).…”
Section: Roof Materials and Characteristicsmentioning
confidence: 92%
See 2 more Smart Citations
“…Other metals that have been studied but reported to be of low or less severe concentrations include cadmium, chromium, nickel and selenium (Förster, 1999;Melidis et al, 2007;Mendez et al, 2011). Other studies observed that the concentrations of Mg, Na, K, nitrate, nitrites, chloride, sulphate and ammonium were not significantly different among free fall rainwater , asbestos and Fe-Zn and aluminium metal sheets (Adeniyi and Olabanji, 2005;Mendez et al, 2011). In other studies, high concentration of nitrates and sulphates in roof runoff were largely attributed to fossil fuel combustion rather than roof materials (Mouli et al, 2005;Evans et al, 2006;Melidis et al, 2007;Gikas and Tsihrintzis, 2012).…”
Section: Roof Materials and Characteristicsmentioning
confidence: 92%
“…Several studies have demonstrated roof runoff contamination by physical, chemical and biological contaminants (Förster, 1998;Garnaud et al, 1999;Zhong et al, 2001) as well as microbiological contaminants (Corden and Millington, 2001;Jones and Harrison, 2004;Evans et al, 2006). Contamination mechanisms include air-borne and atmospheric deposition, direct leaching of metal constituents from metal sheets, colonisation by various plants and consequently direct weathering of roof material and the leaching of the accumulated particulate organic matter and flora on roof surfaces (Förster, 1999;Chang et al, 2004;Adeniyi and Olabanji., 2005). King and Bedient (1982) attributed leaching of chemical compounds from roofs to the acidic nature of ambient rainfall while Chang et al (2004) report that the rough surfaces and cracks associated with wood shingle roofs trap water, aerosols and debris which promote plant growth, particularly fungi resulting in increased organic matter retention on the roof.…”
Section: Nature and Pathways Of Rainwater Contaminationmentioning
confidence: 96%
See 1 more Smart Citation
“…Runoff from rooftops is often considered unpolluted [10] or at least is of relatively good quality compared with runoff from surface catchments [11]. However, there is still disagreement about the quality of rooftop runoff, ranging from good or acceptable [12,13] to contaminated [14,15], depending on the roofing material, environmental conditions and atmospheric pollution. Subject to basic treatments such as filtration and/or chlorination, as necessary, collected rainwater can be utilized for different non-potable uses, including toilet flushing, washing machine use and garden irrigation (or any other use that does not require high-quality water).…”
Section: Introductionmentioning
confidence: 99%
“…However, results from study roofs indicate that roofing materials can be long-term sources of pollutants. Clarke et al [27] and Adeniyi and Olabanji [28] found that contaminants from a range of roofing materials increased as the roof aged. In leaching studies, a range of roof materials including asphalt shingles, fake slate roofing shingles, and galvanized metal were all sources of lead, zinc, iron, and copper [27].…”
Section: Rooftop Characteristicsmentioning
confidence: 98%